Continuous monitoring of caspase-3 activation induced by propofol in developing mouse brain. Issue 51 (June 2016) - Konno, Ayumi; Nishimura, Akiko; Nakamura, Shiro; Mochizuki, Ayako; Yamada, Atsushi; Kamijo, Ryutaro; Inoue, Tomio; Iijima, Takehiko
Highlights: SCAT3 transgene continuously monitored caspase-3 cleavage in neonatal mouse brain. Caspase-3 pathologically activated at five hours after exposure of propofol. Real-time FRET imaging identified the onset of apoptosis by propofol anesthesia. Abstract: The neurotoxicity of anesthetics on the developing brain has drawn the attention of anesthesiologists. Several studies have shown that apoptosis is enhanced by exposure to anesthesia during brain development. Although apoptosis is a physiological developmental step occurring before the maturation of neural networks and the integration of brain function, pathological damage also involves apoptosis. Previous studies have shown that prolonged exposure to anesthetics causes apoptosis. Exactly when the apoptotic cascade starts in the brain remains uncertain. If it starts during the early stage of anesthesia, even short-term anesthesia could harm the brain. Therefore, apoptogenesis should be continuously monitored to elucidate when the apoptotic cascade is triggered by anesthesia. Here, we describe the development of a continuous monitoring system to detect caspase-3 activation using an in vivo model. Brain slices from postnatal days 0–4 SCAT3 transgenic mice with a heterozygous genotype (n = 20) were used for the monitoring of caspase-3 cleavage. SCAT3 is a fusion protein of ECFP and Venus connected by a caspase-3 cleavable peptide, DEVD. A specimen from the hippocampal CA1 sector was mounted on a confocal laser microscope and was continuously superfused with artificial cerebrospinal fluid, propofol (2, 6-diisopropylphenol, 1 μM or 10 μM), and dimethyl sulfoxide. Images were obtained every hour for five hours. A pixel analysis of the ECFP/Venus ratio images was performed using a histogram showing the number of pixels with each ratio. In the histogram of the ECFP/Venus ratio, an area with a ratio > 1 indicated the number of pixels from caspase-3-activated CA1 neurons. We observed a shift in the histogram toward the right over time, indicating caspase-3 activation. This right-ward shift dramatically changed at five hours in the propofol 1 μM and 10 μM groups and was obviously different from that in the control group. Thus, real-time fluorescence energy transfer (FRET) imaging was capable of identifying the onset of apoptosis triggered by propofol in neonatal brain slices. This model may be a useful tool for monitoring apoptogenesis in the developing brain.